The Euro Area's common pool problem revisited: Has the Single Supervisory Mechanism ameliorated forbearance and evergreening? - Sven Steinkamp; Aaron Tornell; Frank Westermann (Osnabrück University, Institute of Empirical Economic Research, 2017)
The Single Supervisory Mechanism was introduced to eliminate the common-pool problem and limit uncontrolled lending by national central banks (NCBs). We analyze its effectiveness. Second, we model how, by forbearing and providing refinancing credit, NCBs avoid domestic resolution costs and, instead, share potential losses within the Euro Area. This results in "evergreening" of bad loans. Third, we construct a new evergreening index based on a large worldwide survey administered by the ifo institute. Regressions show evergreening is significantly greater in the Euro Area and where banks are in distress. Finally, greater evergreening accompanies higher growth of NCB-credit and Target2-liabilities.
Keywords: F33; F55; E58; 330; Single Supervisory Mechanism; Evergreening; Non-performing Loans; Common-pool Problem